NILAI-NILAI PENDIDIKAN AKHLAK DALAM SURAH LUQMAN DAN APLIKASINYA PADA PEMBELAJARAN PAI - Nurul Huda (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2021)
In this globalization era, the progress of technology has positive and negative impact, the moral decadence, the lost of noble characters, the lack of politeness, respecful and appreciating others. Dealing with this, human must learn Islamic Education especially about Islamic morals. This study is to identify the values of Islamic moral education at Surah Luqman and the implementation for teaching Islamic Education of verse 12-20. This study is qualitative research in the form of library research. The main data are surah Luqman verse 12-20, and the secondary data are books and other related sources. This study shows that the values of Islamic moral education at Surah Luqman verse 12-20 contain the basic of relationship between human and God, among human, and between human and nature. The implementation for teaching Islamic Education is about bad and noble characters toward oneself, parents, God, among human, and nature. It is implemented in Islamic elementary school, Islamic Junior High School, and Islamic Senior High School.